Ayres sensory integration ® implementation in Malaysian occupational therapists : challenges and limitations - Farah Samsu Rahman; Masne Kadar; Dzalani Harun (Penerbit Universiti Kebangsaan Malaysia, 2022)
One of the most popular interventions provided by occupational therapists for pediatric clients is Ayres Sensory Integration® (ASI). Strict fidelity measures consisting of procedural and structural elements must be adhered to when using it. These fidelity measures distinguish Ayres Sensory Integration® from other sensory-based interventions. This study involved the development of a survey instrument and outlined the challenges that Malaysian occupational therapists face when using Ayres sensory integration® (ASI). The questionnaire development involved the processes of assessing its validity and reliability. A total of 161 occupational therapists working in various healthcare settings responded to the survey by answering a self-administered questionnaire. The results identified eight themes or issues: (1) Inadequate Training, (2) Resource Issues, (3) Physical Constraints, (4) Time Constraints, (5) Limited Information/ Support Provided By Family, (6) Limited Support From Management, (7) Limited Information/Support Provided By Suppliers, and (8) Issues in Implementing Evidence-Based Practice. Identifying the challenges of implementing ASI is an important aspect of improving occupational therapy assessments and interventions, which would establish the effectiveness of the interventions provided.